Economic preferences and cognitive abilities among teenagers in Spain - Mónica Vasco; Antonio Alfonso; Andreu Arenas; Antonio Cabrales; José A. Cuesta; Antonio M. Espín; María Paz Espinosa; Teresa García-Muñoz; Àlex Izquierdo Nofuentes; Diego Jorrat; Jaromír Kovářík; Pablo Lomas; et al. (Scientific Data)
Abstract This dataset originates from TeensLab, a consortium of Spanish Universities dedicated to behavioral research involving Spanish teenagers. The dataset contains data from 33 distinct educational institutions across Spain, accounting for a total of 5,890 students aged 10 to 23 (M = 14.10, SD = 1.94), representing various educational levels such as primary school, secondary school, sixth form and vocational training. The main dimensions covered in this dataset include (i) economic preferences, (ii) cognitive abilities and (iii) strategic thinking. Additionally, a range of supplementary variables is included alongside socio-demographic factors, capturing data on aspects like physical appearance, mood and expectations, among others.